2020
DOI: 10.1038/s41467-020-19974-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the IRE1 RNase through remodeling of the kinase front pocket by ATP-competitive ligands

Abstract: Inositol-Requiring Enzyme 1 (IRE1) is an essential component of the Unfolded Protein Response. IRE1 spans the endoplasmic reticulum membrane, comprising a sensory lumenal domain, and tandem kinase and endoribonuclease (RNase) cytoplasmic domains. Excess unfolded proteins in the ER lumen induce dimerization and oligomerization of IRE1, triggering kinase trans-autophosphorylation and RNase activation. Known ATP-competitive small-molecule IRE1 kinase inhibitors either allosterically disrupt or stabilize the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Some AIM2 fragments decreased in abundance over time whereas others persisted or even accumulated, suggesting that RIDDLE entails mainly endoribonuclease activity, though exoribonuclease activity against some of the initial products cannot be ruled out. In addition, we treated MDA-MB-231 cells with the previously characterized kinase-directed cellular IRE1α activator, G-9807 62 . This compound induced upregulation of XBP1s, as well as downregulation of the RIDD substrate DGAT2 and the RIDDLE targets TNFAIP8L1 and SIX2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some AIM2 fragments decreased in abundance over time whereas others persisted or even accumulated, suggesting that RIDDLE entails mainly endoribonuclease activity, though exoribonuclease activity against some of the initial products cannot be ruled out. In addition, we treated MDA-MB-231 cells with the previously characterized kinase-directed cellular IRE1α activator, G-9807 62 . This compound induced upregulation of XBP1s, as well as downregulation of the RIDD substrate DGAT2 and the RIDDLE targets TNFAIP8L1 and SIX2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been found that G-1749 is structurally similar to the C 31 H 29 ClN 6 O 3 S (KIRA8); however, the two molecules exert opposing effects on the modulation of RNase activity. G-1749 promotes IRE1 RNase activity via occupation of the kinase pocket proximal to the DFG motif, which leads to a distinct conformation of the activation loop (DFG-in or C-helix in), and this mechanism does not stabilize the dimer interface [ 146 ]. These finding suggests that the IRE1 kinase activation loop may play a role in the regulation of RNase activity.…”
Section: Pharmacological Modulation Of Ire1 Activitymentioning
confidence: 99%
“…IRE1α activation leads to divergent downstream activities including kinase activity, specific Xbp1 splicing activity, and a less specific regulated IRE1-dependent decay (RIDD) activity that degrades ER-associated mRNAs ( Fig. 3 ) ( 66 , 67 ). The RIDD activity of IRE1 has been suggested to degrade INS mRNA itself; interestingly, the protein disulfide isomerase A6 (PDIA6) may counteract this activity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reported examples of UPR pathways leading to cell death are mostly limited to downstream mediators in the IRE1 and PERK pathways. IRE1α hyperactivation can lead to cellular demise in other cell types ( 66 ). As discussed above, IRE1α is a bifunctional enzyme with both kinase and endonuclease activities, the latter resulting in specific Xbp1 splicing or nonspecific RIDD degradation of ER-associated RNAs.…”
Section: Introductionmentioning
confidence: 99%